Penguatan Rantai Pasok pada Sektor Peternakan dan Pertanian Desa Kalijaya Kabupaten Ciamis - Putri Lestari, Suci; Laras Pratiwi; Putri Dian Wulansari; Titin Widyastuti; Agus Supriatman; Anri Kurniawan; Kana Kanari (Universitas Perjuangan Tasikmalaya, 2026)
This community service activity was carried out in Kalijaya Village, Banjaranyar District, Ciamis Regency, which has great potential in the livestock and agricultural sectors, particularly dairy goats and robusta coffee. The partners' main challenges include limited production technology, business management, and supply chain. This program aims to implement sustainable production management through the use of appropriate technologies such as energy-efficient solar panel-based fermenters for fermented feed production and greenhouse dryers for drying coffee beans. In addition, supply chain strengthening is carried out through production management training. This program supports the achievement of SDGs 2 (Zero Hunger) and SDGs 7 (Affordable and Clean Energy), while strengthening the village's economic competitiveness in a sustainable manner.